2011
DOI: 10.1093/ecam/nep165
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PML‐RARα and Oncogenic Signaling Pathways by Chinese Herbal Mixture Tien-Hsien Liquid in Acute Promyelocytic Leukemia NB4 Cells

Abstract: Tien-Hsien Liquid (THL) is a Chinese herbal mixture that has been used worldwide as complementary treatment for cancer patients in the past decade. Recently, THL has been shown to induce apoptosis in various types of solid tumor cells in vitro. However, the underlying molecular mechanisms have not yet been well elucidated. In this study, we explored the effects of THL on acute promyelocytic leukemia (APL) NB4 cells, which could be effectively treated by some traditional Chinese remedies containing arsenic trio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…These herbal combinations are believed to act synergistically to harmonize beneficial effects and to neutralize or minimize the toxic or adverse effects of individual constituent herbs. Recently, numerous efforts have been made to investigate the mechanisms of action of Chinese herbal formulae using modern scientific methodology [3–5] . In‐vitro and in‐vivo studies on the individual herbs or constituents of classic formulae have been reported and many herbal medicines have immunomodulatory or antioxidant effects that may offer clinically relevant therapeutics for patients with disorders associated with ageing [6,7] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These herbal combinations are believed to act synergistically to harmonize beneficial effects and to neutralize or minimize the toxic or adverse effects of individual constituent herbs. Recently, numerous efforts have been made to investigate the mechanisms of action of Chinese herbal formulae using modern scientific methodology [3–5] . In‐vitro and in‐vivo studies on the individual herbs or constituents of classic formulae have been reported and many herbal medicines have immunomodulatory or antioxidant effects that may offer clinically relevant therapeutics for patients with disorders associated with ageing [6,7] …”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous efforts have been made to investigate the mechanisms of action of Chinese herbal formulae using modern scientific methodology. [3][4][5] In-vitro and in-vivo studies on the individual herbs or constituents of classic formulae have been reported and many herbal medicines have immunomodulatory or antioxidant effects that may offer clinically relevant therapeutics for patients with disorders associated with ageing. [6,7] The exclusively old-world genus Ferula, belonging to the family Apiaceae, has some 130 species distributed throughout the Mediterranean area and Central Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments reported that TXL had inhibitory effects on different carcinomas. 3,4 However, the mechanisms of action of TXL on antiproliferation, antimetastasis, and reversion of MDR on HT29 colon cancer have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al tested an aqueous extract of THL in APL NB4 cells and found that the extract could cause cell cycle arrest and induce apoptosis [25]. An ethyl acetate/nhexane extract of THL, however, was found to be 100 times more potent than THL, suggesting that the active anticancer components in THL are relatively hydrophobic.…”
Section: Getting the 'Sovereign' And The 'Minister' Into The Patient: Cmentioning
confidence: 99%